'I was always made fun of for being fat': first-hand accounts of bullying in children's football. (2nd November 2021) - Flores Aguilar, Gonzalo; Prat Grau, Maria; Ventura Vall-Llovera, Carles; Ríos Sisó, Xènia
ABSTRACT: Objetives: To explore perceptions of bullying in children's football (8-13 years) based on the experiences of players, families, and coaches. Method: We conducted a multiple case study. Participants from four football clubs and one coaching academy in Catalonia (Spain) were selected to take part in nine focus group sessions (three for each group: players, families and coaches). Data from the sessions were analyzed by content analysis. Findings: Four main categories were identified: (1) type of bullying, (2) causes, (3) sites of occurrence, and (4) feelings and emotions towards bullying. These have included a series of direct quotes to reflect the main contributions made by the three sets of participants (players, parents, and coaches) based on their most significant experiences. Conclusions: The accounts of the participants show the existence of a wide range of bullying situations and experiences and highlight the need for immediate action towards the prevention and eradication of bullying in children's football.